Exploring Sustainability in Wineries: Evaluating Food Safety and Environmental Management Aligning with the Farm to Fork Strategy - Jesús López-Santiago; Amelia Md Som; Fahmi Asyadi Bin Md Yusof; Fernando R. Mazarrón; María Teresa Gómez-Villarino (Agriculture, 2024)
The Farm to Fork (F2F) Strategy, a key initiative of the European Commission under the European Green Deal, strives to make the European Union’s (EU) economy sustainable. Focused on the food system, the F2F Strategy prioritizes sustainability in agriculture, eco-friendly practices, biodiversity preservation, and climate change mitigation. It targets high food safety (FS) and environmental management (EM) standards across the Agri-food Supply Chain (ASC). Addressing sustainability challenges in the wine industry, this study delves into the Wine Value Chain (WVC). Emphasizing the intricate sustainability interplay within the WVC, this study concentrates on FS and EM to ensure the long-term viability of wine production. The primary goal is to create a comprehensive sustainability evaluation method for wineries, incorporating performance indicators from FS and EM components. The methodology involves assessing Food Safety Management Systems (FSMSs), evaluating Environmental Management Systems (EMSs), investigating contamination risks, and synthesizing results into a sustainability matrix. Findings highlight commendable FS practices, such as widespread Hazard Analysis and Critical Control Point (HACCP) adoption and underscore the need for increased EM focus. Notable figures include a 76.2% adoption of the HACCP system and 68.8% of wineries implementing an EMS. Performance indicators become critical for sustainability assessment, forming the cornerstone to gauge the industry’s effective sustainability management aligned with the F2F Strategy. This study stresses the holistic integration of FS and EM practices, providing insights into workforce engagement, regulatory compliance, and sustainable objectives. This research offers a tool for evaluating and advancing sustainability in the wine industry culminating in a sustainability matrix.